2014
DOI: 10.1063/1.4894266
|View full text |Cite
|
Sign up to set email alerts
|

Plasmons in molecules: Microscopic characterization based on orbital transitions and momentum conservation

Abstract: In solid state physics, electronic excitations are often classified as plasmons or single-particle excitations. The former class of states refers to collective oscillations of the electron density. The random-phase approximation allows for a quantum-theoretical treatment and a characterization on a microscopic level as a coherent superposition of a large number of particle-hole transitions with the same momentum transfer. However, small systems such as molecules or small nanoclusters lack the basic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(87 citation statements)
references
References 74 publications
(74 reference statements)
3
84
0
Order By: Relevance
“…This correlation is analogous to the nearly-linear relationship between metal nanorod plasmon wavelength and nanorod length and is in agreement with the effect of spatial confinement of a charge distribution. 22,29 We also observed a linear redshift with increasing index of refraction of the surrounding environment. 30 .…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…This correlation is analogous to the nearly-linear relationship between metal nanorod plasmon wavelength and nanorod length and is in agreement with the effect of spatial confinement of a charge distribution. 22,29 We also observed a linear redshift with increasing index of refraction of the surrounding environment. 30 .…”
mentioning
confidence: 74%
“…17,18 Insights from recent Time-Dependent Density Functional Theory [18][19][20] (TDDFT) and Random Phase Approximation 21,22 (RPA) theoretical work imply that molecular-scale systems support some excitation modes which are indeed collective in nature. The description of a molecular plasmon as a collective electronic excitation rather than a single-electron transition, is supported by three primary attributes: (1) The strong dependence on the electron-electron interaction strength; (2) The excitation 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 being a superposition of many elementary single-electron excitations (i.e.…”
mentioning
confidence: 98%
“…coupled with transition densities showing oscillating dipolar charge distributions (13,30,31), this is indicative of resonances exhibiting collective electron motion.…”
Section: Significancementioning
confidence: 85%
“…While many properties of nanoscale plasmons are well described by classical electromagnetic theory, in the few-atom quantum limit this description breaks down for the systems that still exhibit plasmonic behavior (10,11), thus requiring a fully quantum treatment. From a quantum-mechanical perspective, plasmons can be described as coherent superpositions of individual electron-hole pair transitions that emerge when the Coulomb interaction between excited states is switched on (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…However, at the nanoscale, single-particle and plasmonic excitations are intrinsically mixed [18], and how to recognize a plasmonic excitation is still an unsolved problem.A few approaches have been recently proposed attempting to classify the plasmonic character of the excitations of nanosystems. [11,[19][20][21][22][23][24] In particular, Bernadotte et al [11] formulated, in the framework of time-dependent density-functional theory (TDDFT), a scaling approach based on the different dependence of the energies of the excitations of nanosystems on the Coulomb kernel. Along this line, Krauter et al[23] demonstrated that the electronic wave function of plasmons, at the time-dependent Hartree-Fock level, is described by the superposition of several electron configurations, i.e.…”
mentioning
confidence: 99%